The impact of regulating occupational pensions in Europe on investment and financial stability - Adrien Amzallag; Daniel Kapp; Christoffer Kok (European Central Bank (ECB), 2014)
This study examines the European Commission's 2011 call for advice to the European Insurance and Occupational Pensions Authority (EIOPA) on the improvement of the Institutions for Occupational Retirement Provision (IORP) Directive (the “IORP Directive”). Specifically, it uses both the EIOPA final advice to the Commission and its quantitative impact study as a basis for answering the following questions: first, what would be the likely impact of the changes proposed to the IORP Directive, in particular minimum solvency requirements, the introduction of risk-based solvency capital requirements, on IORP investment strategies in the short and long term? Second, what would be the impact, if any, of these proposals on financial stability, in particular as regards possible pro-cyclical IORP investment behaviour? The main findings of the study are that the proposed solvency capital requirement framework could lead to IORPs shifting their investment allocations towards a greater proportion of “low-risk” asset classes. However, the impact is likely to vary extensively across EU countries, in line with national pension legislation, demographic profiles, the macro-financial situation and cultural preferences. Nevertheless, the study finds some empirical support to suggest that even the announcement of the proposed revisions, which have in the meantime been deferred, may already have led to some de-risking of some IORPs. Furthermore, some pro-cyclicality of IORPs' investment strategies could be expected should these proposals be adopted, although the exact outcomes will depend on their precise calibration, especially regarding counter-cyclical adjustments.
Keywords: F41; F31; E50; 330; financial regulation; financial stability; Institutions for Occupational Retirement Provision